PENGARUH PEMBAGIAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI BPS KABUPATEN SUMEDANG - Dadang Priyatna; Iis Gusrini; Taufik (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2020)
The purpose of the research conducted is to find out the Effect of Labor Division on the Effectiveness of Employee Work in the Central Statistics Agency (BPS) of Sumedang Regency. The method used in this research is a quantitative research method that is used in research based on the philosophy of positivism with the aim of testing established hypotheses. In this study, researchers used inferential descriptive data analysis techniques to describe or describe the data that has been collected as is by making conclusions that apply to the public. The sampling technique used is a saturated sampling technique, with a population of 33 people. Based on the results of the study, it can be described that the Division of Labor Achievement of The Division of Labor in the office of the Central Statistics Agency (BPS) of Sumedang Regency with the dimensions of activity details, the existence of task details, the existence of task burdens given, having an understanding of tasks, the provision of equal tasks, the placement of appropriate employees, and the assessment of work results that produce a percentage of 77.79%, and can be categorized well. There is a positive and significant relationship between the Division of Labor and the Effectiveness of Employee Work in the office of the Central Statistics Agency (BPS) of Sumedang Regency. This is evidenced by the result of the acquisition of t_hitung price greater than the table t or 5,663>2,0399. So it can be concluded that hypothesis zero (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning that there is a division of labor with the effectiveness of employee work in the office of the Central Statistics Agency (BPS) of Sumedang Regency. Achievement of Employee Work Effectiveness in the office of the Central Bureau of Statistics (BPS) sumedang regency with dimensions of organizational characteristics, environmental characteristics, worker characteristics, as well as management policies and practices that produce a percentage of 84.45% and can be categorized very well.